Evaluation of the Impact of Islamic Education Courses on the Responsibility of Students of Shiraz University of Medical Sciences - Shamsaei, Maryam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
One of the courses that can be used in universities to familiarize students with responsibility is Islamic education courses. These courses are culture-building and human-building courses that can play an essential role in the education of young people and the cultural construction of society by promoting Islamic culture. For this reason, the curriculum planners of Islamic education courses should focus their efforts on designing curricula that meet the needs of students and especially teach responsibility skills from a religious-religious aspect. The present research was carried out using a descriptive survey method on 248 people who had taken Islamic education courses. In this research, a stratified random sampling method was used. The data collection tool was a researcher-made questionnaire in the form of several questionnaires in the three dimensions of insight, attitude, and behavior, and answers were on a five-point Likert scale. The content and structure validity of the questionnaire was confirmed by experts and its reliability coefficient was estimated using Cronbach's alpha coefficient of 0.86. Data analysis was done at the inferential level (one-sample t-test, independent t-test, analysis of variance) using SPSS software. The content analysis of Islamic education courses in line with the impact of these courses on the insight, attitude, and behavior of students towards responsibility, shows that the average score measured is 19.04 out of 40, which indicates an impact of about 50%. The results of the present research show that the main task of Islamic education groups is to teach responsibility and skills to students, which requires a fundamental review and the development of a comprehensive document on the evolution of Islamic education courses